Avaliação tomográfica dos côndilos mandibulares durante o uso de aparelho intraoral para o tratamento da síndrome da apneia obstrutiva do sono - Gurgel, Marcela Lima (2018)
Obstructive Sleep Apnea Syndrome (OSAS) is a public health problem and is currently considered a chronic, progressive, incapacitating disease, presenting a high mortality rate and cardiovascular morbidity. One of the OSAS treatment modalities is the use of oral appliance (OA) of mandibular advancement. These devices are useful for keeping the pharynx open during sleep, but are also potentially capable of inducing changes in the position of the mandibular condyles. The purpose of the study was to evaluate and quantify the positional changes of the mandibular condyle when using intraoral devices by means of tomographic images of the temporomandibular joints, as well as to evaluate if the possible changes in the condylar positions influence the polissonographic parameters of OSAS. Casuistry: Twenty-three patients with a polysomnographic diagnosis of mild / moderate OSAS were screened from the ambulatory of respiratory sleep disorders of the UFC Medical School. Methodology: The study was divided into three consecutive phases: initial evaluation (without OA), sequential evaluations and final evaluation (OA in 85% of maximal mandibular advancement). Measurements in the temporomandibular joint were performed from images obtained from Cone-Beam Computed Tomography prior to the installation of the OA and after reaching 85% of maximal mandibular advancement. In these two moments, polysomnographic records were also made. To obtain the results, the data from the study were submitted to the Kolmogorov-Smirnov normality test and compared by means of paired t-tests and Pearson's correlation (p <0.05, SPSS 20.0). Results: Changes in mandibular condyles position were observed in all patients (p <0.001), with the right (+ 7.67 ± 3.55) and left (+ 7.82 ± 3.39) condyles advancing, as well as extrusion, (+ 3.76 ± 1.46) and (+ 3.27 ± 1.24) respectively. There was a statistically significant decrease in the Apnea and Hypopnea Index (AHI) (p <0.001) and minimal oxyhemoglobin saturation (p = 0.015) with the use of the mandibular advancement device. It was not possible to establish a correction between the condylar advancement/extrusion and the polysomnographic parameters (AHI, mean and minimal oxyhemoglobin saturation). Conclusion: The use of oral appliance promoted a repositioning of the mandibular condyles and an improvement in the polysomnographic parameters. However, the amount of extrusive and condylar advancement detected did not correlate directly with the improvement of polysomnographic values in the sample studied.